Effects of transformations in the urban structure on the quality of life of city residents in the context of recreation - Hrehorowicz-Gaber Hanna (Bulletin of Geography. Socio-Economic Series)
Accumulating over time, spatial transformations in Kraków have been changing the city’s structure. The contemporary image of the city is creating a new model of life and has a major effect on the functional and spatial conditions for its residents. Life in the city is dictated by the rhythm of daily routines, and the time of leisure has been reduced to a minimum. Less and less frequently are public and semi-private urban spaces used in the traditional manner and their number is decreasing. A considerable role in the decrease in the space for relaxation in the city is played by the purchasing power of money which is winning for itself the space for new residential estates.